2016
DOI: 10.1111/eip.12314
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic identity, racial discrimination and attenuated psychotic symptoms in an urban population of emerging adults

Abstract: Strong ethnic group affiliation and connection may serve a protective function for psychosis risk in racially discriminating environments and contexts among REM young adults. The possible social benefits of strong ethnic identification among REM youth who face racial discrimination should be explored further in clinical high-risk studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 51 publications
5
37
0
Order By: Relevance
“…A total of 35,726 participants took part in the studies included in the review (regarding overlapping samples, the studies considering the largest sample sizes were included in the total). Four of the studies involved clinical samples (n = 1017) [9,[35][36][37] and the remaining twenty recruited from non-clinical populations (n = 34,709) [11,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]; thirteen used eight different epidemiological samples (AESOP, EMPIRIC, Fourth National Survey of Ethnic Minorities, MEDINA, NAPLS 2, NEMESIS, NSLASS and NSAL). Within the twenty studies that reported the sex of the participants, 53% were female (regarding overlapping samples, the studies considering the largest sample sizes were included in the total).…”
Section: Sample and Design Characteristics Of Eligible Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 35,726 participants took part in the studies included in the review (regarding overlapping samples, the studies considering the largest sample sizes were included in the total). Four of the studies involved clinical samples (n = 1017) [9,[35][36][37] and the remaining twenty recruited from non-clinical populations (n = 34,709) [11,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]; thirteen used eight different epidemiological samples (AESOP, EMPIRIC, Fourth National Survey of Ethnic Minorities, MEDINA, NAPLS 2, NEMESIS, NSLASS and NSAL). Within the twenty studies that reported the sex of the participants, 53% were female (regarding overlapping samples, the studies considering the largest sample sizes were included in the total).…”
Section: Sample and Design Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…Also, there were no racial differences in the number of APPS-distress endorsed Racial discrimination was associated with APPS-distress and remained significant after adjusting for age (β = .105, p < .001). Bootstrapping analyses suggested that the relationship between racial discrimination and APPS-distress was partially mediated by RS-scores (Rejection Sensitivity Questionnaire-Race; participants concerns and expectations of rejection based on their race) Anglin et al (2016), USA a [39] At least 70% of the student sample experienced one type of perceived discrimination, and a positive significant relationship between perceived discrimination and positive psychotic symptoms (r = 0.211, p < 0.001) Additionally, the relationship between discrimination and positive psychotic symptoms differed based on participant's commitment and exploration of their ethnicity, i.e., ethnic identity (e.g., low ethnic identity, moderate ethnic identity and high ethnic identity Perceived ethnic discrimination was significantly higher in the UHR group compared to health controls, t = 3.63, p < 0.001 Positive correlation between perceived ethnic discrimination and persecutory paranoia in virtual reality for the whole sample (r = 0.25, p = 0.009), but not in individuals at UHR risk (r = 0.119, p = 0.360), or healthy controls (r = 0.212, p = 0.180). Logistic regression found that perceived discrimination was not a significant predictor of paranoid ideation in virtual reality for the whole sample (p = 0.25) or the UHR group (p = 0.95).…”
Section: Is There a Relationship Between Discrimination And Specific mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that examine perceived discrimination by outgroups may assist in understanding the role of prejudice and identity in psychosis. In one of the few studies that has examined ethnic identity and discrimination, it was found that possessing a stronger ethnic identity protects people from developing psychosis in discriminatory environments (Anglin, Lui, Espinosa, Tikhonov, & Ellman, 2016). Research on the rejection-identification model (Branscombe, Schmitt, & Harvey, 1999) suggests that while perceptions of prejudice are associated with reduced wellbeing, prejudice perceptions also increase minority group identification, self-esteem, and outgroup hostility when they are stable and pervasive (Branscombe et al 1999;Schmitt, Spears, & Branscombe, 2003).…”
Section: Recommendations For Future Researchmentioning
confidence: 99%